High Prevalence of the I278T Mutation of the Human Cystathionine β-Synthase Detected by a Novel Screening Application - Linnebank, Michael; Homberger, Anja; Junker, Ralf; Nowak-Goettl, Ulrike; Harms, Erik; Koch, Hans G. (Thrombosis and Haemostasis, 2001)
Classical homocystinuria due to cystathionine beta-synthase deficiency is one of the disorders revealing a high risk of thromboembolic events and vascular disease. This autosomal-recessively inherited metabolic disorder is considered to be rare with an estimated prevalence of 1:130,000 in the German population. In this study, we developed a novel multiplex PCR generating allele specific fragment lengths to analyse individual genotypes of the two most frequent cystathionine beta-synthase alterations, the I278T mutation, which is worldwide found on up to the half of homocystinuric alleles, and the adjacent polymorphism 844ins68. Screening of 200 unrelated German control subjects revealed a frequency of heterozygosity of 1.5% for I278T corresponding to a calculated frequency of homozygosity of 1:17.800. Our data indicate that homocystinuria due to cystathionine β-synthase deficiency is a frequently unrecognized disorder resulting in a high risk of thromboembolic events.
Keywords: Homocystinuria; homocysteine; cystathionine β-synthase; mutation screening